Meningkatkan Hasil Belajar Menggunakan Media Audio Visual dalam Pembelajaran Tata Surya Kelas V SD - Zuliani, Rizki; Karunina, Melita; Asrifah, Diah Nur (Lembaga Yasin AlSys, 2023)
This study aims to improve student learning outcomes in learning the Solar System in class V SD by using audio-visual learning media. This research was conducted on fifth grade students at SDI Alexandria Tangerang City. This research is a classroom action research using descriptive qualitative and quantitative methods. This research was conducted using the model developed by Kurt Lewin, in which there were four stages, namely planning, acting, observing, and reflecting. Data collection techniques in this study include observation, pre-test, action and post-test. The results of the study in cycle I showed an increase in student learning outcomes by 25% from prasikulus. In cycle II there was an increase in student learning outcomes by 41% from cycle I. This shows the influence of audio-visual media in learning student learning outcomes in class V SDI Alexandria learning of the Solar System.